The Makinaugalingon an index to Iloilo's historical past in relation to national and world events, 1913-1941 - Piamonte, Rosalinda P. (1980)
This is an index to all issues of Makinaugalingon, a newspaper published in Iloilo from 1913-1941. During this period, several vernacular newspapers came out but it was only the Makinaugalingon which stayed longest in the scene. Responsible for its publication was a nationalistic man and writer, Rosendo Mejica who was a respected name and political figure in Iloilo during those times.